Dental emergencies - Corbett, Ian (Ian P.); Greenwood, M. (Mark) (Chichester, West Sussex : John Wiley & Sons, 2012)
Dental Emergencies is a readily accessible guide to the treatment and management of dental emergencies for everyday use in clinical practice. Replete with clinical examples and step-by-step procedures, the book distills essential information on traumatic injuries, pain, and oral lesions into a succinct, highly valuable reference. Written by an expert in the field, the book covers the full range of the dental emergencies beginning with clinical examination and assessment of potential complications. Later chapters outline key considerations in pain management, including various presentations of.
1. Introduction, Infection Control and Prescribing -- Introduction to the dental emergency clinic -- Infection and infection control -- Prescribing -- Conclusions -- Further reading -- 2. History Taking and Clinical Examination of Patients on a Dental Emergency Clinic -- Introduction -- History taking -- Patient examination -- Special tests -- Record keeping -- Consent -- Conclusions -- Further reading -- 3. Radiology and the Dental Emergency Clinic -- Introduction -- Patients in pain -- Trauma radiology -- Looking at radiographs -- Conclusions -- Further reading -- 4. Acute Oral Medical and Surgical Conditions -- Introduction -- Oro-facial swelling -- Blistering disorders of the oral mucosa -- Oral ulceration -- Disturbed oro-facial sensory or motor function -- Haemorrhage -- Other acute conditions -- Bony pathology -- Summary -- Further reading -- 5. Restorative Dental Emergencies -- Introduction -- General principles -- Pain management -- Infections and soft tissue problems -- Crack, fracture and mobility of teeth and dental restorations -- Fractured and loose implants -- Fractures and swallowing of removable prostheses -- Conclusions -- Further reading -- 6. Acute Presentations of Chronic Oro-Facial Pain ConditionsIntroduction -- Oro-facial pain history -- Examination of patients with oro-facial pain -- Special investigations for oro-facial pain -- Presentation, investigations and initial management of acute non-odontogenic oro-facial pain -- Further reading -- 7. Traumatic Injuries to the Teeth and Oral Soft Tissues -- Assessment of the traumatised patient -- Management of traumatic dental injuries -- Injuries to the hard dental tissues and the pulp -- Injuries to the hard dental tissues, the pulp and the alveolar process -- Injuries to the periodontal tissues -- Dento-alveolar fracturesConclusions -- Further reading -- 8. Pain Relief in the Dental Emergency Clinic -- Introduction -- General mechanism of pain -- Distribution of pain fibres in the mouth and jaws -- Sources of pain in the mouth and jaws -- Control of pain -- Psychology of pain -- Medication -- The ladder of analgesia -- Avoiding problems in prescribing analgesics -- Further reading -- 9. Management of the Special Needs Patient -- Introduction -- Commonly seen conditions -- Assessment -- Medical history in the patient with special needs -- Informed consent -- Examination -- Factors to consider in treatment -- Conclusion -- 10. Making a ReferralIntroduction -- When to refer -- How to refer -- Where to refer -- The referral letter -- Urgency -- Cancer referrals -- Copies of the referral letter -- Summary -- Further reading -- 11. Medical Emergencies in the Dental Emergency Clinic -- Principles of Management -- Introduction -- Contents of the emergency drug box -- The'ABCDE' approach to an emergency patient -- Airway (A) -- Use of defibrillation -- Principles of management after the initial treatment of a medical emergency -- Conclusions -- Further reading -- 12. Examples of Specific Medical Emergency Situations -- Introduction -- Vasovagal syncope (simple faint).
Includes bibliographical references and index.
Keywords: Dental care; Dental emergencies; HEALTH & FITNESS -- Oral Health; MEDICAL -- Dentistry -- General; Dental care; Dental emergencies; Dental Care -- methods; Emergencies; Emergency Treatment -- methods; Electronic books